2015
DOI: 10.1016/j.rser.2014.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the causal linkages between nuclear energy, renewable energy and economic growth in developed and developing countries

Abstract: a b s t r a c tThis article investigates the causal relationship between two types of energy variables and economic growth using dynamic simultaneous-equation panel data models for 17 developed and developing countries. Our results indicate that there is a unidirectional causality running from nuclear consumption to economic growth in Belgium and Spain, while a unidirectional causality running from economic growth to nuclear consumption is supported in Bulgaria, Canada, Netherlands, and Sweden. A bidirectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(98 citation statements)
references
References 42 publications
8
70
3
2
Order By: Relevance
“…However, using the same model to simulate the relationship between renewable energy development and economic growth, Kahia et al [17] showed that long-term and short-term two-way causality between them may exist. This suggests that when studying the relationship between energy structure and economic development in different countries, even with the same research methods and models, the results are significantly different [18,19]. The main reason is that economic phenomena are complex and variable, leading to nonlinear relationships between economic variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, using the same model to simulate the relationship between renewable energy development and economic growth, Kahia et al [17] showed that long-term and short-term two-way causality between them may exist. This suggests that when studying the relationship between energy structure and economic development in different countries, even with the same research methods and models, the results are significantly different [18,19]. The main reason is that economic phenomena are complex and variable, leading to nonlinear relationships between economic variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Looking at the investment climate for publicly traded alternative energy companies, Henriques and Sadorsky (2008) find that stock prices of those companies respond more to a shock affecting technology stock prices (or a technology index) than to oil prices. Sadorsky (2009a), Salim and Rafiq (2012) and Omri et al (2015) use oil prices as a determinant of 2914…”
Section: Crude Oil and Renewable Energymentioning
confidence: 99%
“…For example, through empirical analysis of the energy structure and economic growth of the G20 countries, Sikder et al [29] have suggested that renewable energy has different effects on the economic output of different countries; clean energy use can significantly boost gain in countries such as Argentina, Italy, and the US. Similarly, by comparing the fossil energy and non-fossil energy consumption in countries with an economic difference, Omri et al [30] proposed that there is a one-way causal relationship between renewable energy consumption and economic growth in developed countries such as Japan and the Netherlands.…”
Section: Can the Development Of Clean Energy Promote Economic Growth?mentioning
confidence: 99%